CONSUMER LEGAL EFFORTS DUE TO ABUSE OF CIRCUMSTANCES (MISBRUIK VAN OMSTANDIGHEDEN) IN STANDARDIZED AGREEMENTS - Celina Tri Siwi Kristiyani (NOTARIIL Jurnal Kenotariatan, 2020)
Private law develops with the dynamics of community needs. Law Number 8 of 1999 concerning Consumer Protection Law is a form of regulation aimed at balancing the rights and obligations of both consumers and business actors. But in reality, consumers are always the weaker party; the injured party is due to a more inferior position. The form of consumer losses that often occur is the existence of standardized agreements containing elements of misuse (misbruik van omstanddigheden). As a result, the consumers agree not to an agreement in "good faith", but what has been agreed is that the will of the business actor intends to harm consumers by abusing the situation. This study aims to 1) know the categories of circumstances abuse in standardized agreements that harm consumers, 2) know the legal efforts that consumers can do due to abuse of circumstances (misbruik van omstanddigheden) in standardized agreements. The method used is juridical normative that is using primary legal materials and secondary legal materials to analyze the problem, but it is contextualized by the dynamics of standardized agreements in the global era. The results obtained that in the current global era the standardized agreements with the abuse of the circumstances are increasingly diverse. If it is proven that there is an abuse of circumstances, then the effort is cancelling the agreement. Minimizing the misuse of circumstances in the standardized agreement requires the participation of all parties, consumers, businesses and the government.